Word-formation Paradigmas a Unit of the Confrontative Analysis of Close-Related Languagues (Russian-Polish Correspondences) - Zych, Anna (Respectus Philologicus, 2003)
The article is devoted to the problem of describing word-formation level of two related languages using the so-called word-formation paradigm as a unit of comparison. The analysis is directed to the word-formation paradigms of Polish and Russian adjectives implying colour. First, such an approach gives an opportunity to obtain interesting data concerning the functioning of the word-formation system of a language, second, in the case of confrontation, to reveal similarities and differences between the compared languages, third, to define the basis of similarities and differences.
Keywords: linguistics; comparative linguistics; comparative Russian-Polish linguistics; word-formation; complex word-formation units; word-formation paradigm